Obesity-Related Behaviors among Poor Adolescents and Young Adults: Is Social Position Associated with Risk Behaviors? - Ritterman Weintraub, Miranda Lucia; Fernald, Lia C.; Goodman, Elizabeth; Guendelman, Sylvia; Adler, Nancy E. (Frontiers in Public Health, 2015)
Highlights Different measures of social position capture unique dimensions of relative rank among youth. Youth-specific measures of social position may be important in identifying the most at-risk for obesity. Lower social status youth are more likely to be at-risk for obesity-related behaviors compared to those with a higher rank. This cross-sectional study examines multiple dimensions of social position in relation to obesity-related behaviors in an adolescent and young adult population. In addition to using conventional measures of social position, including parental education and household expenditures, we explore the usefulness of three youth-specific measures of social position – community and society subjective social status and school dropout status. Data are taken from a 2004 house-to-house survey of urban households within the bottom 20th percentile of income distribution within seven states in Mexico. A total of 5,321 Mexican adolescents, aged 12–22 years, provided information on obesity-related behaviors (e.g., diet, physical activity, sedentary behavior) and indicators of subjective and objective social position. A parent in each household provided information on socioeconomic status of the parent and household. Ordinal logistic regressions are used to estimate the associations of parental, household and adolescent indicators of social position and obesity-related risk behaviors. Those adolescents with the highest odds of adopting obesity risk behaviors were the ones who perceived themselves as lower in social status in reference to their peer community and those who had dropped out of school. We found no significant associations between parental education or household expenditures and obesity-related risk behaviors. Immediate social factors in adolescents’ lives may have a strong influence on their health-related behaviors. This study provides evidence for the usefulness of two particular measures, both of which are youth-specific. Adolescents and young adults who have dropped out of school and those with lower perceived relative social position within their community are more likely to be at-risk for obesity-related behaviors than those with higher relative social position. We conclude that youth-specific measures may be important in identifying the most at-risk among relatively homogeneous populations of youth.